Taskiyatun Nafs Intervention To Increase Religiosity In Adolescents With Social Anxiety - Ina, Ina (Jurnal Studi Agama, 2025)
A condition or symptom that often arises in adolescents that needs further attention is social anxiety. This contains the fact that there is a need for guidance, including through psychological stages regarding how taskiyatun nafs intervention is always applied. Especially, how this condition affects the mental and physical in adolescents. This research uses an Islamic psychological approach and how it is relevant to taskiyatun nafs intervention in increasing religiosity. The research method, using qualitative literature review research by collecting and reviewing 11 journals regarding taskiyatun nafs intervention, increasing religiosity, social anxiety disorder in adolescents and the concept of Islamic psychology. The results showed that adolescents with social anxiety have a disorder that occurs in the emotional realm, which is characterized by feelings of fear, or continuous worry, this needs good attention. This stage is in the taskiyatun nafs intervention, namely takhalli, tahalli and tajalli which are stages that can help them develop self-awareness, mental quality, religious coping, quality of life and spiritual awareness. As in Islamic psychology regarding the problematic lives of adolescents, there is a need for in-depth guidance in a holistic healing process so that adolescents can find a way to overcome and manage their social anxiety in a balanced and integrated way.